Dampak Pendidikan Terhadap Pertumbuhan Ekonomi Provinsi Kalimantan Timur - , NURANI CITRA ADRAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The effort in increasing economic growth is closely related to available resources. We donât just rely on the natural resources but also need to pay attention to human resources. Human resources development as capital needed to increase the economy. Therefore itâs important to develop human resources through education in order to foster the productivity of each individual as a driver of economic growth. The aim of this study is to find out the impact of education, labour, and education expenditure on economic growth in East Kalimantan Province during the period 2001-2012. The research is expected to provide an ilustration on the impact of education in buliding human capital as a fuction of the production on economic growth, especially in East Kalimantan Province. This research employed panel data technique with random effect model estimation. The empirical results show that education and labour have a positive and significant impact on economic growth. On the contrary, education expenditure does not provide significant value to the economic growth. The estimates of panel model suggest that 1 percent increase in education will contribute to about 2.84 percent increase in economic growth. Keywords: education, labour, education expenditure, economic growth